Microbiome Analysis and Pharmacovigilance After Inhaled Glucocorticoid: Oral Dysbiosis With the Isolation of Three Rothia Species and Subsequent Sjögren’s Syndrome - Zdziarski, Przemysław; Paściak, Mariola; Gamian, Andrzej (Frontiers in Pharmacology, 2022)
Background: Treatment of respiratory tract diseases with inhaled glucocorticoids is a form of therapy which has been used for many years. It shows lower potency of side effects; nevertheless, microbiome change, sinopulmonary dysbiosis, secondary immunodeficiency and immunomodulatory effects are underestimated. Last guideline recommendations introduce the use of empirical antibiotic and/or multiplying inhaled glucocorticoids in therapeutic intervention of asthma and chronic pulmonary obstructive disease. Aims and objectives: The aim of the study was description of simple, universal and cost-effective method of microbiome analysis for clinical trials. Such a general method for monitoring pharmacovigillance should be widely available and reliable. Methods: The study material included two kinds of swabs, taken from the same mouth ulcerations of patients with asthma treated with a temporary quadruple dose of fluticasone. The microbiological investigation was performed and identification of the isolates was carried out using the MALDI-TOF-MS Biotyper. Results: The analysis of dry swab demonstrated the presence of typical oral bacteria (Neisseria spp., Streptococcus spp.), alongside with the potentially pathogenic Actinomyces spp. and three different Rothia species, identified simultaneously: R. aeria, R. dentocariosa and R. mucilaginosa. Although quadrupled dose of corticoids was discontinued and ulcer healing was observed, the patients required topical therapy for maintained xerostomia. Progressive systemic autoimmunity (seronegative Sjögren’s syndrome with major organ involvement) was observed later. Conclusions: Topical steroids (especially in quadrupling dose) require attention to safety, immunomodulatory and microbiological outcome. They showed systemic side effects: microbiome alteration, humoral (IgG) immunodeficiency and systemic autoimmunity. Isolation of three species of Rothia from a patient with mouth ulcers after steroid therapy suggests their participation in infectious and inflammatory processes. The proposed methodology with using MALDI-TOF-MS may be a prototype approach for microbial diagnostics in clinical trials of immunomodulatory drugs.